معرفة التدفق النفسي لدى طلبة الجامعة - مجيد العتابي عبدالله; ماجد محمد زينب (Journal of College of Education, 2020)
The aim of this research is to identify: 1- Degree of psychological flow among university students. 2 - the level of significance of differences of psychological flow according to variables (type, specialization, grade). In order to achieve the objectives of the research, the researcher prepared a measure of psychological flow, and applied the sample to the statistical analysis sample (350) students, and after confirming the validity of the scale through the indicators of honesty and consistency, the researcher applied the scale on the sample (375) students, And statistical processing. Using a single sample tester, a single-variance analysis, and Pearson correlation coefficient, the results were as follows: 1_ University students enjoy psychological flow and statistical significance. 2_ There is no statistically significant difference in psychological flow according to variables (gender, specialization) while there is a difference for the variable of the school stage. In the light of the results achieved and to complement the research, the researcher recommended a set of recommendations and proposals